A computational model of axial piston swashplate pumps. (September 2017) - Fornarelli, F.; Lippolis, A.; Oresta, P.; Posa, A.
Abstract: Variable displacement hydraulic machines offer a very promising alternative and energy saving solution for many applications in mobile machines, mobile robots and other applications. In the present paper an axial piston swashplate pump will be theoretically analyzed and explained using the software AMESim in order to estimate the piston friction force and volumetric efficiency loss without hardworking experimental tests. The present paper is aimed at analyzing the forces acting on the swash plate in stationary and non-stationary conditions, in order to optimize the main design parameters of the control actuators of a variable displacement pump. The behavior of the machine is analyzed and presented at different angular velocities and pressure regimes.